Co-Creating News Oases in Media Deserts - Ferrier, Michelle Barrett (2023)
The Media Deserts Project is a research effort to map and model the changing media landscape in the United States. Media deserts are defined as geographies lacking fresh, daily news and information. Using circulation data of US print newspapers, emerging hyperlocal online news sites in digital networks, and broadband access data from the Federal Communication Commission, the Media Deserts Project maps these changes using geographic information systems down to the zip code level, making visible local communication systems and gaps. To develop community-centered news and information solutions, this research team used community-based research practices, where students engaged with residents, local business leaders, health, education, and other administrators to examine the communication needs of three specific communities in Southeast Ohio. We centered our efforts on building relationships with community members and designing localized media tools. We learned key insights that we believe may travel well into other projects using community-based engagement, participatory design, and co-creation practices.